Multicriteria optimization methodic of the aerospace system conceptual parameters - Климова, А. С. (Problems of Informatization and Control, 2009)
The article is devoted to the decision of actual scientific task from the increase efficiency of the perspective aerospace system design. The problem is solved by mathematical simulation of the multicriteria optimization methodic of the aerospace system conceptual parameters